# Thank you so much in advance!

Verify each identity. Work one side (the harder side) Please show me the work

sin θ +cos θ cot θ= csc θ

Cos^2 θ + 1 =2cos^2 θ +sin^2 θ

## sin T + cos T cot T

sin T + cos T cos T/sin T

(sin^2 T + cos^2 T ) /sin T

1/sin T

which is csc T

=============================

LOL, subtract cos^2 T from both sides

1 = cos^2 T + sin^2 T

what else is new :)

## To verify the given identities, we need to manipulate one side of the equation to make it equal to the other side. Let's start with the first identity:

sin θ + cos θ cot θ = csc θ

To work on the harder side, let's simplify the right-hand side (RHS) of the equation.

RHS = csc θ

Using the reciprocal identity, csc θ = 1/sin θ, we can rewrite the RHS:

RHS = 1/sin θ

Now, let's focus on the left-hand side (LHS) of the equation and manipulate it to match with the RHS.

LHS = sin θ + cos θ cot θ

We can rewrite cot θ as cos θ/sin θ using the reciprocal identity, cot θ = cos θ/sin θ:

LHS = sin θ + cos θ * (cos θ/sin θ)

Now, let's simplify the expression on the LHS:

LHS = sin θ + (cos^2 θ / sin θ)

Next, we need to find the common denominator between sin θ and cos^2 θ. The common denominator is sin θ, so let's multiply the first term by cos^2 θ / cos^2 θ:

LHS = (sin θ * cos^2 θ / cos^2 θ) + (cos^2 θ / sin θ)

Now, let's simplify further:

LHS = (sin θ * cos^2 θ + cos^2 θ) / cos^2 θ * sin θ

Now, factor out cos^2 θ from the numerator:

LHS = (cos^2 θ * (sin θ + 1)) / cos^2 θ * sin θ

Finally, cancel out the cos^2 θ terms in the numerator and denominator:

LHS = (sin θ + 1) / sin θ

Now, we can see that the LHS matches the RHS, which means the identity is valid.

sin θ + cos θ cot θ = csc θ is verified.

Let's move on to the second identity:

cos^2 θ + 1 = 2cos^2 θ + sin^2 θ

We'll work on the harder side, which is the left-hand side (LHS):

LHS = cos^2 θ + 1

To simplify this expression, let's subtract 2cos^2 θ from both sides:

LHS - 2cos^2 θ = cos^2 θ + 1 - 2cos^2 θ

Simplifying further:

LHS - 2cos^2 θ = 1 - cos^2 θ

Now, let's rewrite the right-hand side (RHS) using the trigonometric identity, sin^2 θ + cos^2 θ = 1:

RHS = sin^2 θ + cos^2 θ = 1

Substituting back into the equation:

LHS - 2cos^2 θ = RHS

cos^2 θ + 1 - 2cos^2 θ = 1

Next, let's combine like terms on the left-hand side:

-cos^2 θ - cos^2 θ + 1 = 1

Simplifying further:

-2cos^2 θ + 1 = 1

Now, subtract 1 from both sides:

-2cos^2 θ = 0

Next, divide both sides by -2 to solve for cos^2 θ:

cos^2 θ = 0

Taking the square root of both sides:

cos θ = ±√0

Since the square root of 0 is 0, we have two solutions:

cos θ = 0

Now, we can use these solutions to verify the identity. Plugging in cos θ = 0 into both sides of the equation:

LHS = cos^2 θ + 1

LHS = 0^2 + 1

LHS = 0 + 1

LHS = 1

RHS = 2cos^2 θ + sin^2 θ

RHS = 2(0^2) + sin^2 θ

RHS = 2(0) + sin^2 θ

RHS = 0 + sin^2 θ

RHS = sin^2 θ

As the LHS equals 1 and the RHS equals sin^2 θ, it is clear that the identity is not valid for all values of θ. The identity only holds true when cos θ = 0.

I hope this explanation helps you verify the given identities!